Morphological and genetic data from Cnemidocarpa verrucosa sensu lato - Ruiz, Micaela Belén; Taverna, Anabela Jesús; Servetto, Natalia; Sahade, Ricardo Jose; Held, Christoph
The Southern Ocean is one of the most isolated marine ecosystems, characterized by high levels of endemism, diversity and biomass. Ascidians are among the dominant groups in the Antarctic benthic communities, thus recording the evolutionary patterns of this group is crucial to improve our current understanding on the assembly of this polar ocean. In this study, we studied the genetic variation within Cnemidocarpa verrucosa sensu lato, one of the most widely distributed and abundant ascidians in Antarctica. Using a mitochondrial and a nuclear gene (mtCOI and 18S), the phylogeography of fifteen populations distributed along the Antarctic Peninsula and South America (Burdwood Bank/MPA Namuncurá) was characterized, where the bimodal distribution of the genetic distance suggested the existence of two species within the nominal C. verrucosa. When re-evaluating morphological traits to distinguish between genetically defined species, the presence of basal disc in one of the genotypes allowed to differentiate the species. Fil: Ruiz, Micaela Belén. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Taverna, Anabela Jesús. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Servetto, Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Córdoba. Instituto de Diversidad y Ecología Animal. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas Físicas y Naturales. Instituto de Diversidad y Ecología Animal; Argentina Fil: Sahade, Ricardo Jose. Consejo Nacional de Investigaciones ...